Pancreatic islets isolated from Î²2 adrenergic receptor knockout mice show reduced insulin secretion in response to nutrients - doi: 10.4025/actascibiolsci.v35i3.15842 (Acta Scientiarum. Biological Sciences, 2013)
Activation of Î²2 adrenergic receptors by catecholamine or catecholamine-mimetic substances may enhance insulin secretion. We herein investigated KCl- and nutrient-stimulated insulin secretion in pancreatic islets isolated from Î²2 knockout (Î²2KO) mice. Î²2KO mice showed reduced body weight, fasting hypoglycaemia associate to a similar fasting insulinemia compared to control. Î²2KO mice also showed reduced glucose tolerance despite the higher sensitivity to insulin. Glucose-induced insulin secretion was impaired in pancreatic islets isolated from Î²2KO mice. Leucine-induced (20mM) insulin secretion was diminished in pancreatic islets isolated from Î²2KO mice when compared to control one. The depolarizing effect of KCl on insulin secretion was also impaired in pancreatic islets from Î²2KO mice. These results suggested a possible role of Î²2 adrenergic receptors on nutrient-induced insulin secretion.